ANTIFUNGAL ACTIVITY OF Punica granatum LINN EXTRACTS AGAINST Malassezia pachydermatis - Chamilete, Sophia Aparecida Morro; Matsumoto, Leopoldo Sussumu; Delfino, Fernanda; Pirajá, Guilherme Villa; DA SILVA, Regildo Márcio Gonçalves [UNESP]; de Mello PEIXOTO, Erika Cosendey Toledo (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2023)
Malassezia pachydermatis causes external otitis, often affecting dogs, and control methods for this microorganism have been resistant to synthetic antifungals. Therefore, this study evaluated the antifungal activity of aqueous extracts of Punica granatum Linn (AEP) fruit peel dehydrated (AEPd) and in natura (AEPn) against Malassezia pachydermatis. The M. pachydermatis samples were from the Microbiology Laboratory of the State University of Northern Paraná (UENP), PR, Brazil. The strains were identified and replicated after inoculation in the Sabouraud dextrose medium. Subsequently, the P. granatum extract was obtained through different extraction methods: cold, water bath, decoction, and infusion. Each test was run fivefold at 10, 20, 30, 40, and 50% after 10, 20, and 30 minutes. The sensitivity of isolates was determined with the Kirby-Bauer disc diffusion method and indicated by an inhibition zone larger than 15 mm. The results were evaluated with a 2x3x6 factorial study design, ANOVA, and Tukey's test at 5% significance. AEPn showed antifungal activity on M. pachydermatis strains, and AEPd did not present an inhibitory influence at any concentration and time. Extraction by decoction was the most efficient, followed by water bath, cold, and infusion. The extracts at a 50% concentration showed the best results, but all other doses determined an inhibition zone larger than 15 mm. Thus, AEP showed a significant therapeutic potential for controlling M. pachydermatis.
Keywords: External otitis; Medicinal plants; Pomegranate